Serial Cervical Length Evaluation in Low-Risk Women with Shortened Cervical Lengths in the Midtrimester: How Many Will Dilate Prior to 24 Weeks? - Zafman, Kelly B.; Rebarber, Andrei; Fox, Nathan S. (American Journal of Perinatology, 2020)
Objective To determine what proportion of women with a short cervical length (CL) without a history of spontaneous preterm birth (SPTB) will ultimately be dilated at <24 weeks.Study Design This is a retrospective cohort study of women with singleton pregnancies with a short CL (≤25 mm) between 16 and 22 weeks' gestational age (GA). We excluded women with a history of SPTB. We examined the progression of women with short CL based on the CL measurement and GA at diagnosis. The primary outcome was cervical dilation or spontaneous delivery <24 weeks.Results A total of 163 women were included, of whom 27 (16.6%) were ultimately dilated and 4 (2.5%) had pregnancy loss by 24 weeks. The median GA at diagnosis of short CL was 195/7 (range: 15–22) weeks. Women with a CL <15 mm were more likely to have cervical dilation or loss prior to 24 weeks than women whose CL was 15 to 25 mm (42.5 vs. 11.9%, <0.001, adjusted odds ratio: 3.72, 95% confidence interval: 1.52–9.09). GA at diagnosis was not associated with risk of progression.Conclusion In women with a short CL without a history of SPTB, the risk of dilation or pregnancy loss <24 weeks is significant, approaching 50% for women with a CL <15 mm.
Keywords: cervical length; short cervix; preterm birth